Spondylolysis as a cause of low back pain in swimmers - Nyska, M.; Constantini, N.; Cale-Benzoor, M.; Back, Z.; Kahn, G.; Mann, G. (International Journal of Sports Medicine, 2000)
Low back pain (LBP) has recently become a common complaint in swimmers. The differential diagnosis of LBP in swimmers includes muscle and ligament sprains, Scheuerman disease, herniated disc, facet joint injury, tumors, infections, and spondylolysis. Although spondylolysis or listhesis is a frequent injury in the athlete, mainly in weightlifters, wrestlers, gymnasts, divers and ballet dancers, it is infrequently reported in swimmers. We have recently encountered four adolescent elite swimmers who complained of low back pain and were diagnosed as having spondylolysis. Three of the patients were either breast-strokers or butterfly swimmers. Plain radiography demonstrated the lesion in two patients. Increased uptake in bone scan was noted in all patients. CT was performed only in two patients and revealed the lesion in both. One patient was diagnosed within two weeks, and the diagnosis in the others was deferred for 2-7 months. The patients were treated successfully by reducing the intensity of their training program and the use of a corset for at least three months. Repeated hyperextension is one of the mechanisms for spondylolysis in athletes as is the case in breast-strokers and butterfly style swimmers. LBP in swimmers should raise the suspicion of spondylolysis. Plain radiography and bone scan should be performed followed by SPEC views, CT, or MRI as indicated. If the case is of acute onset as verified by bone scan, a Boston or similar brace should be used for 3 to 6 months in conjunction with activity modification and optional physical therapy. Multidisciplinary awareness of low back pain in swimmers, which includes trainers, sport medicine physicians, and physical therapists, should lead to early diagnosis and appropriate treatment.